Peningkatan Kapasitas dan Deteksi Dini HIV/AIDS Pada Remaja di Kota Baubau - Wa Ode Sitti Justin; Ahmad Amiruddin; Sudirman Pabokori; Sri Ernawati; Syastriani Isna Putri Syarif (Abdimas Universal, 2022)
HIV/AIDS is one of the deadliest diseases for which a cure has not been found, so innovation is needed to cure people with HIV/AIDS. AIDS is a manifestation of HIV infection that significantly suppresses a person's immune function. The aim is to increase the knowledge of adolescents and to detect the HIV status of adolescents in Baubau city. The method used is by way of counseling and examination. The results obtained are that there is an increase in adolescent knowledge and the results of the HIV-AIDS rapid test show that 98% of adolescents are aware and willing to carry out an early examination to determine their HIV status as an effort to prevent HIV transmission.